Identification, Confirmation, and Replication of Novel Urinary MicroRNA Biomarkers in Lupus Nephritis and Diabetic Nephropathy. (1st September 2017) - Cardenas-Gonzalez, Mariana; Srivastava, Anand; Pavkovic, Mira; Bijol, Vanesa; Rennke, Helmut G; Stillman, Isaac E; Zhang, Xiaolan; Parikh, Samir; Rovin, Brad H; Afkarian, Maryam; de Boer, Ian H; Himmelfarb, Jonathan; et al.
Abstract: BACKGROUND: The prevalence of chronic kidney disease (CKD) is increasing, leading to significant morbidity and mortality. Kidney biopsy remains the gold standard for diagnosing the underlying etiology of CKD, but the procedure carries complication risks. The aim of this study was to identify novel noninvasive biomarkers correlating with kidney function and histopathology in biopsy-proven CKD patients. METHODS: We profiled 2402 urinary microRNAs (miRNAs) to identify and confirm differentially expressed miRNAs associated with kidney function and histopathology in patients with diabetic nephropathy (n = 58) or lupus nephritis (n = 89), important etiologies of CKD, compared with healthy controls (n = 93 and 119, respectively). Top performing miRNAs were then measured in 2 independent multi-institutional cohorts of patients with diabetes mellitus with (n = 74) or without nephropathy (n = 71) and systemic lupus erythematosus with (n = 86) or without (n = 37) nephritis. RESULTS: In patients with diabetic nephropathy, miR-2861, miR-1915-3p, and miR-4532 were down-regulated (>10-fold, P < 0.0001) and were associated with estimated glomerular filtration rate ( P < 0.01) and interstitial fibrosis/tubular atrophy ( P < 0.05). The c -statistics for miR-2861, miR-1915-3p, and miR-4532 were 0.91, 0.86, and 0.85, respectively. In lupus nephritis patients, miR-3201 and miR-1273e were down-regulated (>3-fold, P < 0.0001) and associated with endocapillary glomerular inflammation ( P < 0.01), with c -statistics of 0.97 and 0.91, respectively. CONCLUSIONS: We have identified novel miRNAs that correlate with histopathological lesions and functional markers of kidney damage to facilitate sensitive, specific, and noninvasive detection of diabetic nephropathy and lupus nephritis.